TOXIC RELATIONSHIP SEBAGAI PEMICU TERJADINYA KEKERASAN TERHADAP PEREMPUAN (Studi Kasus Pada Empat Korban Toxic Relationship) - Munir , Abdul; Afriani, Nelly (UIR PRESS, 2021)
Toxic relationships that can trigger violence against women can be caused by two factors, namely internal factors and external factors. The purpose of this study was to determine the factors that trigger the emergence of violence experienced by women in toxic relationship problems. This study uses qualitative research methods, namely the method used to examine the condition of natural objects with the researcher as the key instrument which is carried out by interviewing the resource person. Referring to the two theories used, namely Radical Feminism and Victimization, to see how women are targeted as victims of violence in toxic relationship issue